Frequency of Attention-Deficit Hyperactivity Disorder (ADHD) in Patients with Congenital Heart Diseases (CHD) at NICVD Karachi, Pakistan - Sobia Memon, Greesh Kumar Maheshwari, Mehak Muhammad Ashfaq, Maham Khan, Zainab Shamim, Zaynab Khan, M. Saadullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The study aimed to assess the frequency and impact of attention-deficit hyperactivity disorder (ADHD) on behavior, social-emotional development, intelligence, and overall quality of life among school-aged children with congenital heart diseases (CHD). Methodology: A descriptive cross-sectional study was undertaken at the National Institute of Cardiovascular Diseases (NICVD) between July 2021 to August 2021. A total of 100 CHD patients aged 6 to 18 were assessed using the non-probability purposive sampling technique. The data was collected using a questionnaire comprising SNAP-IV 26 Scale that is a screening tool for ADHD. The collected data was entered and analyzed by using Statistical Package for Social Sciences (SPSS) v 24.0. The statistical analysis was carried out with a confidence interval set at 95% and no p-value was determined as a threshold of statistical significance, owing to the qualitative nature of the data. Result: The study comprises n=100 CHD patients, aged 6 to 18 with the mean age ± standard deviation of 11.18 ± 3.914, and males and females stratifiable into 56% and 44% respectively. The ADHD screening identified n=22 (22%) subjects as highly suspected of having ADHD with no statistically significant gender difference (n=10 females vs. n=12 males). The study revealed Ventricular Septal Defect (VSD) to be the most common (28%) congenital heart defect across the in-patient and out-patient settings. VSD is followed by Atrial Septal Defect (ASD) at 24%, Tetralogy of Fallot (TOF) at 22%, Atrioventricular Septal Defect (AVSD) at 19%, and Aortic Stenosis (AS) in 7% of the patients. Out of the 25% facing comorbidities, hypertension dominated the subset of 23%. Conclusion: This study suggests that children with CHD are at an increased risk of developing ADHD, the hyperactive and the combined subtype in particular, compared to the healthy population. About 22 percent of the subjects manifested a typical clinical picture of an ADHD patient with mostly living a ‘somewhat difficult’ life. Keywords: Children, Congenital Heart Disease, CHD, Attention-Deficit Hyperactivity Disorder, ADHD, Ventricular Septal Defect, VSD, Atrial Septal Defect, ASD